Pembuatan Dan Pengolahan Limbah Sampai Pada Pembuangan IPAL Atau Sanimas Pada Lingkungan : Case on Desa Imbi, Distrik Jayapura Utara, Kota Jayapura, Papua - Daniel Ayub Dawan (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
The Community Sanitation Program (SANIMAS) in Imbe Village treats domestic wastewater in densely populated residential areas and low-income communities (MBR) using a wastewater treatment installation system (IPAL). The IPAL SANIMAS Program's location in Imbi Village, North Jayapura District, Jayapura City, Papua must be researched by comparing numerous Sanimas to assess their success or failure. The benchmarking approach is a strategy for improving performance through comparison in order to obtain an inside view so that best practices may be implemented. The steps taken include measuring performance in the form of values from the Work Terms of Reference Assessment Sheet (LPKAK), which consists of technical indicators, and comparing them to see which location has the highest indicator value, while locations with low indicator values will be given priority. The site of Imbi Village, North Jayapura District, has the highest indication value of 100 percent, according to benchmarking data. The recommendation for the location at the Imbi Village location, North Jayapura District is to drain the settling basin on a regular basis and provide operational and maintenance costs in the form of government donations/assistance funds, while development preparation is being carried out at the Imbi Village location, North Jayapura District. maturing, extending residency duration at WWTPs, carrying out maintenance in compliance with applicable SOPs, strengthening community capacity and post-construction management, and improving coordination and responsibility division in the Sanitation Working Group (POKJA).